Relationship between perceived physical self-concept and grade in physical education: The mediating role of test anxiety. (September 2021) - Mascret, Nicolas; Rey, Olivier; Danthony, Sarah; Maïano, Christophe
Abstract: The first aim of this cross-sectional study was to examine the relationships between adolescents' physical self-perceptions (physical condition, sport competence, physical attractiveness, physical strength) and grade in Physical Education (PE). The second aim was to investigate the potential indirect effect of PE test anxiety variables (worry, self-focus, bodily symptoms, somatic tension, perceived control) on the relationships between physical self-perceptions and grade in PE. French adolescent students ( N  = 412; 225 girls) completed scales assessing physical self-perceptions and PE test anxiety. The results highlighted that grade in PE was positively predicted by sport competence, somatic tension, and perceived control, and negatively predicted by bodily symptoms in PE. The results also showed that bodily symptoms have a significant negative indirect effect on the relationships between perceived sport competence and grade in PE, and between physical strength and grade in PE. A significant indirect effect of somatic tension on the relationship between sport competence and grade in PE has also been found. Highlights: Adolescents' physical self-concept positively predicts grade in PE. Grade in PE is negatively predicted by test anxiety. Test anxiety mediates the relationships between physical self-concept and grade. Boys have higher physical self-concept and lower test anxiety scores than girls.